Caries dental y pH salival en pacientes de 12 a 17 años atendidos en la IPRESS Bellavista Nanay 2023 - Herrera Meza, Maria Teresa (2023)
The objective of this study was to evaluate the relationship between salivary pH and dental caries in adolescent patients treated at the IPRESS Bellaviata Nanay. The study was quantitative type. The design is non-experimental, cross-sectional, correlational. The sample consisted of 200 adolescent patients treated at the Ipress Bellavista Nanay. The most important results were: The male sex presented an acid salivary pH of 33.8%, and the female sex presented an acid salivary pH of 31.7%, the neutral salivary pH is 65% in the male sex and the neutral salivary pH was 68.3% in the female sex, basic salivary pH in our study was 1.2% in the male sex, the basic salivary pH was 0% in the female sex. There is a relationship between the age of the patients and their salivary pH (p=0.002) There is no relationship between salivary pH and dental caries (p=0.905)